Production Methods, Salt Quality, and Farmers’ Income: Comparing Traditional and Geomembrane-Based Salt Farming - Prasetyo Nugroho; Aprilina Susandini; Arie Setyo Dwi Purnomo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Salt production in Madura is carried out using both traditional and modern methods involving geomembrane technology. These differences significantly affect production costs and farmers’ income. Therefore, this research aims to more clearly and in greater detail identify differences in the cost structure, income, quantity, and quality of salt produced by traditional and modern production methods. This study employed a qualitative descriptive method, and the respondents were salt farmers from these areas. The sampling technique used was snowball sampling. The collected data were processed using simple calculations and then analyzed to obtain the research findings and conclusions. The findings show that most salt farmers in Sampang, Pamekasan, and Bangkalan use modern production methods based on geomembrane technology, while a small number still rely on traditional methods. Modern methods are more effective, producing higher yields and better salt quality with a greater chance of meeting K1 standards. Although modern production requires higher costs, it generates greater profits compared to traditional methods. The results suggest that wider adoption of modern geomembrane-based production methods can improve efficiency, salt quality, and farmers’ incomes.